2020
DOI: 10.1371/journal.pone.0240533
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of ginsenoside Rg3 on cancer stemness and mesenchymal transition in breast cancer via regulation of myeloid-derived suppressor cells

Abstract: Ginsenoside Rg3 (Rg3) has been studied in several cancer models and is suggested to act through various pharmacological effects. We investigated the anticancer properties of Rg3 through myeloid-derived suppressor cell (MDSC) modulation in FM3A mouse mammary carcinoma cells. The effects of Rg3 on MDSCs and consequent changes in cancer stemlike cells (CSCs) and epithelial-mesenchymal transition (EMT) were evaluated by diverse methods. MDSCs promoted cancer by enhancing breast cancer stemness and promoting EMT. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…It has been shown that the expansion of MDSCs correlates with tumor burden of BC-bearing patients, and the alteration of MDSC-tumor interaction is considered a promising strategy to combat this disease [242] . Consistently with this observation, Peng et al [243] demonstrated that MDSCs accelerate tumor progression and increase tumor incidence in NOD-scid IL2Rγ null (NSG) mice in vivo. To dissect the underlying molecular mechanism, they observed that MDSCs promote and sustain BCSCs by regulating the crosstalk between STAT3 and Notch signaling in tumor cells.…”
Section: Disrupting Notch-dependent Tumor and Immune Cells Interaction To Overcome Drug Resistancementioning
confidence: 53%
See 2 more Smart Citations
“…It has been shown that the expansion of MDSCs correlates with tumor burden of BC-bearing patients, and the alteration of MDSC-tumor interaction is considered a promising strategy to combat this disease [242] . Consistently with this observation, Peng et al [243] demonstrated that MDSCs accelerate tumor progression and increase tumor incidence in NOD-scid IL2Rγ null (NSG) mice in vivo. To dissect the underlying molecular mechanism, they observed that MDSCs promote and sustain BCSCs by regulating the crosstalk between STAT3 and Notch signaling in tumor cells.…”
Section: Disrupting Notch-dependent Tumor and Immune Cells Interaction To Overcome Drug Resistancementioning
confidence: 53%
“…Indeed, MDSCs secretes IL-6, which induces STAT3 phosphorylation, and activates Notch signaling, which enforces IL-6/STAT3 activation, thereby affecting cancer stemness. Interestingly, the inhibition of these two pathways decreased tumor incidence in vivo [243] .…”
Section: Disrupting Notch-dependent Tumor and Immune Cells Interaction To Overcome Drug Resistancementioning
confidence: 98%
See 1 more Smart Citation
“…Meanwhile, Rg3 has been well-described as a tumor suppressor of breast cancer. It has been found that ginsenoside Rg3 reduces mesenchymal transition and cancer stemness of breast cancer by regulating myeloid-related suppressor cells [ 24 ]. Ginsenoside Rg3 combined with Endostar represses tumor growth of breast cancer cells [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ginsenoside Rg3 serves as a primary ginseng component and presents angiogenesis inhibitory potential in conventional biomedicine (Ahmmed et al, 2019). Rg3 exhibits anti-tumor properties in various cancer models, including lung cancer, breast cancer, and ovarian cancer (Sun et al, 2017;Song et al, 2020). Rg3 has been found to induce apoptosis and repress migration of cancer stem cells (Tang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%